What are best practices for involving family caregivers in interventions aimed at responsive behaviour stemming from unmet needs of people with dementia in nursing homes: a scoping review - Miharu Nakanishi; Jenny T van der Steen; Wilco P Achterberg; Hanneke J A Smaling; Petra E M Tasseron-Dries (BMJ Open, 2023)
Objectives This study aimed to determine best practices for involving family caregivers in interventions aimed at preventing and reducing responsive behaviour stemming from unmet needs, including pain.Design Scoping review, reported according to the Preferred Reporting Items for Systematic Reviews, Meta-Analyses extension for Scoping Reviews reporting guideline.Data sources PubMed, Embase, Emcare, Web of Science, COCHRANE Library, PsycINFO, Academic Search Premier and Cinahl searched up to 23 July 2023.Eligibility criteria Studies reporting on family involvement in interventions for nursing home residents with dementia were included.Data extraction and synthesis Two researchers independently extracted the data, followed by a content analysis.Results Of the 1486 records screened, 20 studies were included. Family caregivers were involved in interventions aimed at planning care, life review (eg, documentation of life experiences of their relative), and selecting activities for their relative. Family caregivers preferred an active role in developing optimal care for their relative. Drivers of success and barriers to family involvement centred around three themes: (1) communication between all involved; (2) prerequisites (organisational and other conditions) and (3) personal circumstances (family’s coping and skills).Conclusion Best practices for involving family caregivers in interventions aimed at addressing responsive behaviour in residents with dementia concerned those interventions in which family caregivers were given an important role in managing responsive behaviour. This means that, in order to achieve an active role of family caregivers in the whole care process, their needs must be taken into account.Trial registration number The protocol of the review was regisered at OSF; https://osf.io/twcfq